Exploring the role of healthy dogs as hosts of enterohepatic Helicobacter species using cultivation‐dependent and ‐independent approaches. (14th February 2021) - Ochoa, Sofía; Ojeda, Javier; Martínez, Oscar A.; Vidal‐Veuthey, Boris; Collado, Luis
Abstract: Enterohepatic Helicobacter (EHH) species have been increasingly associated with acute gastroenteritis, inflammatory bowel disease and hepatobiliary diseases in humans. However, their host range and transmission routes are poorly understood. Therefore, the aim of this study was to determine the presence of EHH in healthy dogs using both cultivation‐dependent and ‐independent methods. Three hundred and ninety faecal samples from domestic dogs without gastrointestinal symptoms were analysed between June 2018 and July 2019 in Valdivia (South of Chile). Samples were inoculated on selective medium and in parallel were filtrated over an antibiotic‐free blood agar. Both media were incubated in a microaerobic atmosphere at 37°C for 7 days. Colonies were identified by PCR and phylogenetic analysis. A subset of 50 samples (half of them positive for EHH by cultivation and the remaining half negative) was analysed by PCR‐Denaturing Gradient Gel Electrophoresis (PCR‐DGGE) for direct detection. Cultivation method detected EHH in 15.4% (60/390) of the samples, being the most prevalent species H. canis (5.8%, 23/390) and H. canicola (5.1%, 20/390), followed by H. bilis (3.6%, 14/390) and 'H. winghamensis' (1.3%, 5/390). In contrast, PCR‐DGGE method detected Helicobacter DNA in almost all (96%, 48/50) tested samples. On the other hand, the method used also allowed to isolate other Campylobacterales, in fact 44.3% (173/390) of the samples were positive for Campylobacter upsaliensis (43.3%, 169/390) followed by C. jejuni (2.0%, 8/390). Moreover, two strains that presented Campylobacter ‐like morphology were finally identified as Anaerobiospirillum succiniciproducens . Our results indicate that healthy domestic dogs commonly carry EHH and other Campylobacter species. However, further studies are needed to determine whether and how these Helicobacter and Campylobacter species can be transmitted to humans.